The effect of a fee waiver on the National High School Exam (ENEM) on college attendance prospects - Santos, Gabriel Marcondes dos (2021)
In 2001 the Brazilian Federal Government implemented a fee exemption policy benefiting only final-year public school students taking the National High School Exam (ENEM), a standardized test which is broadly used for college admissions in Brazil. To encourage application, students from public high schools could apply directly from their high schools. The international evidence shows that mandatory and subsidized admission exams increase the number of test takers. Thus, we expect that the fee exemption and the application at schools increase the number of final-year public high school students taking the ENEM test. Nevertheless, we also want to understand if the policy attracted more high-achieving students and affected the highly competitive entrance exam from Universidade Estadual de Campinas (UNICAMP), which uses ENEM scores in the admission process. We find that the fee waiver policy led to a sharp increase of 22.4 percentage points in the share of public high school students taking the ENEM exam (i.e., 447,000 new students, compared with 2000). The impact was more pronounced in poorer, less developed, and smaller municipalities. Moreover, public high school students in the top 1% and 10% of the ENEM score distribution increased after the policy intervention. In the UNICAMP’s admission exam, we find that public high school students are more likely to reach the second stage of the admissions process after the policy, but this did not translate into public high school students being admitted to UNICAMP. More interestingly, we find these last results (i.e., reaching the second stage of the admission process) to highly competitive majors, such as Medicine. Thus, this sizable response to a small per-student exemption suggests that such policies can greatly impact the college admission process.